An Analysis of the Impact of Rents from Non-renewable Natural Resources and Changes in Human Capital on Institutional Quality: A Case Study of Kuwait - Aljarallah, Ruba (International Journal of Energy Economics and Policy, 2021)
Non-renewable energy resources are considered to be an important input for industries that support local industrial production and employment. However, many researchers believe that such resources have a damaging effect on the institutional quality, because this quality has an effect on a country's decision-making mechanisms, and on the human capital, which is usually described as the accumulation of education in a specified population. This collective damage thus impedes economic growth and development. The present study analyses the impact of resource rents from non-renewable energy resources and the human capital on the institutional quality in Kuwait, using an autoregressive distributed lag (ARDL) approach based on data for the period between 1984 to 2018. The results indicate that an increase in rents from non-renewable energy resources has decreased institutional quality, whereas human capital enhances the institutional quality both in the short and long-term. This study concludes that an investment in the human capital could help insulate Kuwait from the damaging effects of over-reliance on the non-renewable energy resource rents. Keywords: Non-renewable Energy Resources; Resource Rents; Institutional Quality; Human Capital; Kuwait; Resource Curse JEL Classifications: F62; O11; O38; O40 DOI: https://doi.org/10.32479/ijeep.11370